Too much information re-examining the Vivares v. St. Theresa's College standard of reasonable expectation of privacy in social media (Philippine Law Journal, 2023)
The right to privacy found under Article IIII, Section 3 of our Constitution is perhaps the most malleable of our constitutional rights. As technological developments challenge traditional societal conceptions of privacy, the right to privacy has evolved from a physical, temporal right primarily tied to property rights, to becoming an independent right encompassing both persons and property. In recent years, it seems that privacy is once again being challenged by the rise of social media, which presents a whole new lacuna of privacy considerations primarily due to the novel, sui generis nature of the internet. Our jurisprudence has yet to sufficiently address these issues, with only one case, Vivares v. St. Theresa's College, tackling the issue of informational privacy in social media. While it is the leading case on the subject, it has formulated an insufficient and problematic standard for determining whether an internet user has exhibited a reasonable expectation of privacy online. Through an exploration of the implications of the Vivares ruling, this paper hopes to demonstrate how drastically our societal conceptions of privacy have changed as a result of social media, and thus argue for a re- formulation of the Vivares doctrine which better accounts for the unique nuances of social media.